Epithelial-to-mesenchymal transition (EMT) to sarcoma in recurrent lung adenosquamous carcinoma following adjuvant chemotherapy - Chai, Chee-Shee; Poh, Mau Ern; Liam, Chong Kin; Mun, Kein Seong; Wong, Chee Kuan; Tan, Jiunn Liang; Loh, Thian Chee; Chin, Ka Kiat (China Lung Oncology Group and John Wiley & Sons Australia, Ltd, 2019)
Adjuvant chemotherapy has long been indicated to extend survival in completely resected stage IB to IIIA non-small cell lung cancer (NSCLC). However, there is accumulating evidence that chemotherapy or chemoradiotherapy can induce epithelial-to-mesenchymal transition (EMT) in disseminated or circulating NSCLC cells. Here, we describe the first case of EMT as the cause of recurrence and metastasis in a patient with resected stage IIB lung adenosquamous carcinoma after adjuvant chemotherapy. We review the literature and explore the possible mechanisms by which EMT occurs in disseminated tumor cells (DTC) or circulating tumor cells (CTC) in response to adjuvant chemotherapy (cisplatin) as a stressor. We also explore the possible therapeutic strategies to reverse EMT in patients with recurrence. In summary, although adjuvant cisplatin-based chemotherapy in resected NSCLC does extend survival, it may lead to the adverse phenomenon of EMT in disseminated tumor cells (DTC) or circulating tumor cells (CTC) causing recurrence and metastasis.